Penggunaan Pendekatan Emo-Demo dalam Edukasi Pencegahan Stunting pada Orang Tua Siswa Taman Kanak-kanak: The Use of the Emo-Demo Approach in Stunting Prevention Education for Parents of Kindergarten Students - Yustiyani Yustiyani; Mochamad Nurmansyah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Stunting is one of many health problems in Indonesia than needs to be addressed through intervention program such as nutrition sensitive program. The objective of this community service program was to improve parental knowledge on stunting prevention using emotional demonstration (emo-demo) approach. The program was held on January 20, 2022, at Legoso kindergarten, South Tangerang city. The program participants consisted of 16 kindergarten student parents. The program blended the lecture and game session using emo demo approach. The emo-demo module was developed based on a guideline by GAIN. The participants characteristics as well as knowledge before and after the program was measured using a set of pre and post-test questionnaire on Google Form. Most of participants were female (93,8%), aged 31-40 years old (75,0%) with diploma or bachelor’s degree (68,8%). Almost all participants have heard about stunting prior to joining this program (93,8%). The information of stunting was obtained from social media/internet (56,3%), television/radio (50,0%) and came from families (31,3%), friends (31,3%), public figures (31,3%) and health care professionals (25%). We found significant improvement of the average participant’s knowledge on stunting from 17,25 ± 5,59 points to 23,58 ± 6,79 points at the end of the program (p=0,02). Emo-demo is one of the methods could be used to educate public especially related to stunting issue. ABSTRAK Stunting masih menjadi permasalahan kesehatan di Indonesia yang membutuhkan penanganan, salah satunya melalui intervensi gizi sensitif. Tujuan kegiatan ini adalah untuk meningkatkan pengetahuan orang tua siswa dalam pencegahan stunting pada anak usia dini dengan menggunakan pendekatan emo-demo. Kegiatan penyuluhan dilaksanakan pada 20 Januari 2022 di TK di Legoso, Tangerang Selatan. Peserta penyuluhan terdiri atas 16 orang tua siswa. Penyuluhan dilakukan dengan metode ceramah dan permainan menggunakan pendekatan emo-demo. Pengembangan modul emo-demo merujuk pada pedoman pengembangan oleh Global Alliance for Improved Nutrition (GAIN). Karakteristik peserta dan pengetahuan sebelum dan sesudah mengikuti penyuluhan diukur menggunakan kuesioner pre dan post-test dengan media Google Form. Sebagian besar peserta adalah perempuan (93,8%), berusia 31-40 tahun (75,0%), dan memiliki pendidikan terakhir diploma/sarjana (68,8%). Hampir seluruh peserta pernah mendengar istilah stunting sebelum mendapatkan penyuluhan (93,8%). Informasi tentang stunting diperoleh dari sosial media/internet (56,3%), televisi/radio (50,0%) dan berasal dari keluarga (31,3%), teman (31,3%), tokoh masyarakat (31,3%) dan tenaga kesehatan (25%). Terdapat peningkatan rata-rata skor pengetahuan peserta yang signifikan dari 17,25 ± 5,59 menjadi 23,58 ± 6,79 setelah mendapatkan penyuluhan (p=0,02). Emo-demo dapat menjadi salah satu metode yang efektif dalam pemberian edukasi bagi masyarakat khususnya terkait stunting.